2001
DOI: 10.1385/ir:24:3:245
|View full text |Cite
|
Sign up to set email alerts
|

Functional Regulation of Immunoproteasomes and Transporter Associated with Antigen Processing

Abstract: The central event in the cellular immune response to invading pathogens is the presentation of non-self antigenic peptides by major histocompatibility complex (MHC) class I molecules to cytotoxic T lymphocytes (CTLs). As peptide binding and transport proteins, MHC class I molecules have evolved distinct biochemical and cellular strategies for acquiring antigenic peptides, providing CTLs an extracellular representation of the intracellular antigen content. Whereas efficient generation of MHC class I binding pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 139 publications
0
8
0
Order By: Relevance
“…A deficit in the expression of genes encoding molecules that play a central role in antigen presentation by MHC class I molecules was seen in our IRF‐1 –/– mice, including beta2 microglobulin, Tap binding protein, proteasome 28 subunit alpha, proteasome subunit beta type 10 and large multifunctional protease 7 (LPM7) 28–30 . The latter three genes encode subunits of the so‐called immunoproteasome, a specialized proteasome dedicated to antigen processing and presentation 59 . Notably, protease 28 alpha subunit knockout mice have impaired cytotoxic and T‐lymphocyte responses and LMP7 knockout mice have decreased expression of MHC Class I molecules with impaired presentation of endogenous antigens 28,60 .…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…A deficit in the expression of genes encoding molecules that play a central role in antigen presentation by MHC class I molecules was seen in our IRF‐1 –/– mice, including beta2 microglobulin, Tap binding protein, proteasome 28 subunit alpha, proteasome subunit beta type 10 and large multifunctional protease 7 (LPM7) 28–30 . The latter three genes encode subunits of the so‐called immunoproteasome, a specialized proteasome dedicated to antigen processing and presentation 59 . Notably, protease 28 alpha subunit knockout mice have impaired cytotoxic and T‐lymphocyte responses and LMP7 knockout mice have decreased expression of MHC Class I molecules with impaired presentation of endogenous antigens 28,60 .…”
Section: Discussionmentioning
confidence: 69%
“…[28][29][30] The latter three genes encode subunits of the so-called immunoproteasome, a specialized proteasome dedicated to antigen processing and presentation. 59 Notably, protease 28 alpha subunit knockout mice have impaired cytotoxic and T-lymphocyte responses and LMP7 knockout mice have decreased expression of MHC Class I molecules with impaired presentation of endogenous antigens. 28,60 The Dec205 gene, downregulated five-fold in IRF-1 -/-mice, encodes a molecule involved in the endocytosis of antigen by dendritic cells, a necessary precondition for MHC Class I antigen presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, one Cluster-B gene, PML , has been identified as a regulator of the immunoproteasome (73). Also, the IFN-driven N-PLS-DA confirmed that genes related to the immunoproteasome [i.e., TAP1 (74) and PSMB8 ( LMP7 ) (70)] can be incorporated into the predictive models.…”
Section: Discussionmentioning
confidence: 74%
“…SGK can reportedly be either upregulated or downregulated in the rodent hippocampus after performance of learning tasks (Donahue et al, 2002;Tsai et al, 2002), and it is proposed that enhanced SGK expression facilitates memory consolidation (Tsai et al, 2002). The oligopeptides generated by proteasomal protein digestion are transported into the endoplasmic reticulum via the antigen transporter complex (Tap1, Tap2, and tapasin), which is physically associated with the proteasome in many cell types (Hwang et al, 2001). Intriguingly, targeted deletion of the Tap1 gene in mice contributes to deficits in synaptic plasticity (Huh et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the oligopeptides generated by proteasomal protein digestion are transported into the endoplasmic reticulum via the antigen transporter complex (Tap1, Tap2 and tapasin). The TAP complex is physically associated with the proteasome in many cell types (Hwang et al, 2001), and, intriguingly, targeted deletion of the Tap1 gene in mice contributes to deficits in synaptic plasticity (Huh et al, 2000). Four genes involved in different stages of proteasome function were selected for additional investigation: psmb9 and psme2, which encode proteasome subunits known to modulate proteasome activity; Tap1, which is physically associated with the proteasome and has been implicated in synaptic plasticity; and SGK, which regulates the access to the proteasome of certain proteins involved in plasticity and is also itself degraded by the proteasome.…”
Section: Validation Of the Influence Of Zif268 On Expression Of Protementioning
confidence: 99%